Enhancing teachers' competencies in information technology through infographics training as an alternative learning media - Maida Norahmi; Maria Arina Luardini; Ristati Ristati; Rezqan Noor Farid; Muhammad Subhan Fikri; Novika Amalia; Sovia Rahmaniah; Dellis Pratika; Siti Munawarah; Windi Fitriyani (University of Merdeka Malang, 2024)
Many teachers struggle to utilize technology to create interactive, creative, and innovative learning media. They often face challenges in selecting and using the wide variety of available learning tools, which leads them to rely on traditional methods such as textbooks. Additionally, the lack of skills in using technology-based media, such as infographics, hinders their ability to enhance the quality of teaching in line with the demands of the digital era. This study aims to describe the implementation of infographic training as an alternative learning media at SMPN Satap 2 Palangka Raya. The training was designed to enhance teachers' competencies in utilizing information technology, especially within the limitations of available resources. Using the Assets-Based Community Development (ABCD) approach, the training leveraged existing facilities such as school laptops, smartphones, and premium Canva accounts. The training activities included an introduction to infographic design, hands-on practice with Canva, intensive mentoring, and an exhibition of participants' works. The results indicate that the training was conducted as planned with active teacher participation, despite technical challenges such as limited internet connectivity. This training also highlighted the importance of sustained support, such as providing adequate technological infrastructure by schools and local governments, to improve the effectiveness of similar programs in the future.